Role of Emotional Intelligence in EFL Learners’ Speaking Accuracy and Fluency - Juraeva Iroda Akhmedovna; Xayrullayeva Sugdiyona (Genius Journals, 2025)
This study examines the relationship between emotional intelligence and speaking English as a foreign language among 240 intermediate-level learners from six universities. Participants completed an emotional functioning inventory and underwent a standardized speaking assessment measuring accuracy and fluency. The results show significant positive correlations between emotional intelligence and the components of speaking ability: self-awareness (r=0.67, p
Keywords: emotional intelligence; English speaking ability; speaking accuracy